Pengembangan Usaha Hidroponik 55 dalam Memproduksi Makanan Olahan Sayuran dan Mewujudkan Program Eco-Eduwisata - Fitri Mailani; Eli Ratni; Donny Eros; Jauharry Jauharry; Mulyanti Roberto Muliantino (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
Hydroponics 55 is an agricultural business that produces healthy vegetables without pesticides and processed food products. Continuous assistance is essential to increase the productivity of developing companies. The purpose of this activity is to assist partners in growing their business, namely in making processed products of Hydroponics 55 by making